The Performance Of Pcm-Enhanced Walls For The Reduction Of Peak Indoor Temperature In Tropical Climate - Al-Absi, Zeyad Amin Abdo Saeed (2021)
Buildings in Malaysia suffer from high indoor temperatures due to the hot and humid tropical climate, which results in extensive use of air-conditioning for cooling. The building sector is one of the main contributors to high energy consumption and the associated greenhouse gases emissions. However, the literature and comfort standards showed that Malaysians have more tolerance for hot weather and that the upper limit of comfort range can reach an average of 30 to 32℃ in naturally conditioned buildings. Therefore, the gap between the indoor temperature level and the required comfort level can be tackled by proper passive design strategies. This study aims to investigate the potential use of the PCMs as a passive cooling strategy for naturally conditioned multi-story residential buildings in Malaysia. Various methods have been implemented in this study, including field measurements in the existing buildings to determine suitable ranges for the PCM’s transition temperatures, simulation investigation and optimization for the PCMs application in walls’ interior surfaces, laboratory experimental work to incorporate the PCMs into the façade’s exterior finishing, and experimental evaluation for the PCM-based exterior finishing under the actual weather condition. The results showed that PCMs with transition temperatures between 26℃ and 30℃ can be suggested for interior applications, while between 30℃ and 36℃ are suggested for exterior finishing applications.